Influence of earthquake spatial variability on differential soil displacements and SDF system response. - Nuti, Camillo (Earthquake engineering & structural dynamics.)
The aim of this study is to develop design criteria, which account for the effects of earthquakes spatial variability. The two simplest forms of this problem are dealt with : differential ground displacements and differential structural displacements, for points and structures separated in space. The structures considered are linear elastic single degree of freedom oscillators. These problems may seem trivial, but some of the codes considered appear improvable on this aspect. First, the mathematical model is set up using basic random vibration theory and the code provisions critically examined. Then, the sensitivity of the ground and structural differential response is assessed. The differential displacements can be mathematically expressed in a straightforward fashion, both for the ground and the structures. These expressions are simple enough to be used as design rules. Comparison with the European and Italian Civil Protection codes shows that these can be improved out this aspect; and, for this reason, the Italian draft code for bridges has been mainly drafted following the results of this study.